A direct carbon solid oxide fuel cell operated on a plant derived biofuel with natural catalyst. (1st October 2016) - Cai, Weizi; Zhou, Qian; Xie, Yongmin; Liu, Jiang; Long, Guohui; Cheng, Shuang; Liu, Meilin
Graphical abstract: A plant-derived biochar, with biologically accumulated chemical elements as catalyst for the Boudouard reaction, is a superior fuel to the all-solid-state direct carbon solid oxide fuel cells (DC-SOFCs), and, it enables DC-SOFCs to be a novel technology, of high efficient, low cost and environmental friendliness, for distributed power generation. Highlights: Orchid leaf char is a good fuel of all-solid-state DC-SOFCs. Performance of DC-SOFC with leaf char is better than that with Fe-loaded carbon. Biologically accumulated Ca in leaf char acts as catalyst for Boudouard reaction. Leaf char with natural Ca performs better than C with Ca added by mechanical mixing. Biochar with natural catalyst provides low cost and low pollutant fuel to DC-SOFCs. Abstract: Biochar derived from orchid tree leaves is utilised as the fuel of a direct carbon solid oxide fuel cell (DC-SOFC), with yttrium stabilized zirconia (YSZ) as electrolyte and cermet of silver and gadolinium doped ceria (Ag-GDC) as the material of both cathode and anode, operating without any liquid medium or feeding gas. The performance of the DC-SOFC operated on the leaf char is higher than that operated on the best reported carbon fuel for DC-SOFCs, Fe-loaded activated carbon. XRD, Raman spectroscopy, SEM and EDX are applied to characterize the leaf char. It turns out that the leaf char is with porous structure and there is much Ca along with some K and Mg uniformly distributing in the leaf char. The effects of the naturally existing alkaline earth metal and alkaline metal and their distribution on the performance of the DC-SOFCs operated on the leaf char are analyzed in detail.